PENGARUH MODEL PEMBELAJARAN QUANTUM LEARNING TERHADAP HASIL BELAJAR IPAS KELAS IV SD SWASTA HKBP TOMUAN PEMATANGSIANTAR - Simanjuntak, Melvin; Imelda Sabrina Sibarani; Agus Tiara Barus (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the influence of the Quantum Learning model on the learning outcomes of IPAS (Science and Social Studies) for fourth-grade students at SD Swasta HKBP Tomuan Pematangsiantar. This research used a quantitative research method with a "Pre-Experimental Design" in the form of a one-group pre-test post-test conducted at the same school. The study involved a population of 20 students, with the entire population also serving as the sample. Data collection was conducted using a test administered twice: a pre-test and a post-test. The data was processed using statistical analysis techniques. The results showed a significance level of 0.01 which is less than the probability of 0.05. The calculated t-value (thitung​=9.452) was greater than the t-table value (ttabel​=1.728). Based on these findings, the null hypothesis (H0​) was rejected and the alternative hypothesis (Ha​) was accepted. This indicates that "there is an influence of the Quantum Learning Model on the learning outcomes of IPAS for fourth-grade students at SD Swasta HKBP Tomuan Pematangsiantar."